2018
DOI: 10.12659/msm.910295
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-183-5p Inhibits Aggressiveness of Cervical Cancer Cells by Targeting Integrin Subunit Beta 1 (ITGB1)

Abstract: BackgroundAccumulating studies demonstrate that microRNAs play crucial roles in multiple processes of cancer progression. Lower levels of miR-183 have ben observed in diverse types of tumors but the mechanism and precise function of miR-183-5p in cervical cancer have largely not been investigated.Material/MethodsThe level of miR-183-5p in different cervical cancer cell lines and clinical tissues was detected qRT-PCR assays. Transwell and wound-healing migration assays were conducted to assess the functional ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 22 publications
1
12
0
Order By: Relevance
“…26 suggesting that miR-183-5p significantly inhibited migration and invasion in cervical cancer cells. 38 It was also shown that increased expression of miR-183-5p promoted apoptosis and suppressed the EMT, proliferation, invasion and migration of human endometrial cancer cells by downregulating Ezrin, a membrane-cytoskeleton linker protein. 39 We also showed that induction of miR-183-5p has been involved in the shikonin-inhibited EMT process via inhibition of Snail and induction of E-cadherin expressions.…”
Section: Dovepressmentioning
confidence: 98%
“…26 suggesting that miR-183-5p significantly inhibited migration and invasion in cervical cancer cells. 38 It was also shown that increased expression of miR-183-5p promoted apoptosis and suppressed the EMT, proliferation, invasion and migration of human endometrial cancer cells by downregulating Ezrin, a membrane-cytoskeleton linker protein. 39 We also showed that induction of miR-183-5p has been involved in the shikonin-inhibited EMT process via inhibition of Snail and induction of E-cadherin expressions.…”
Section: Dovepressmentioning
confidence: 98%
“…MiR-183 can significantly reduce the expression of ITGB1, thereby inhibiting cell migration and adhesion. MiR-183 is downregulated in cervical cancer cell line HeLa, and miR-183 directly regulates the invasion and metastasis of HeLa cells by acting on its target gene ITGB1 [44].…”
Section: Roles Of Mir-183 In Cell Migration and Invasionmentioning
confidence: 99%
“…Here, our data supported the tumor-promoting property of circ_0018289 in cervical cancer. We identified that circ_0018289 bound to miR-183-5p, a potent suppressor in cervical cancer [ 12 , 13 ]. Furthermore, we demonstrated that the circ_0018289/miR-183-5p axis-mediated transmembrane p24 trafficking protein 5 (TMED5) expression impacted cervical carcinogenesis and angiogenesis.…”
Section: Introductionmentioning
confidence: 99%